2005
DOI: 10.1016/j.orthres.2005.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multidrug chemotherapy on bone graft augmented prosthesis fixation

Abstract: Use of combination adjuvant chemotherapies have improved the disease free survival rate of tumor patients significantly. However, studies have shown that chemotherapeutic agents have negative effects on bone graft incorporation and fixation of porouscoated prostheses needed for reconstruction of bone defects after wide resection of malignant tumors. Unilateral resection of a 6-cm segment of the femoral diaphysis and reconstruction with a porous-coated segmental prosthesis was performed in eight mixed-breed dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For those with a good prognosis, ensuring adjuvant treatment does not interfere with the fixation of the reconstruction could ensure a better outcome, as chemotherapy and radiotherapy may interfere with osteointegration. 7,28,31,32 This theoretical concern, however, has not been documented clinically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For those with a good prognosis, ensuring adjuvant treatment does not interfere with the fixation of the reconstruction could ensure a better outcome, as chemotherapy and radiotherapy may interfere with osteointegration. 7,28,31,32 This theoretical concern, however, has not been documented clinically.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]6,7,9,14,[16][17][18]21,[23][24][25][26][27][28][29] Furthermore, the literature does not demonstrate a clear advantage in implant survival when comparing cemented and cementless constructs. Published prosthetic 10-year survival for cemented prosthesis ranges from 30% to 90%, 6,12,19,21,23,33 while 10-year survival for cementless constructs ranges from 25% to 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also exists which has conversely shown bone turnover to be clearly affected by the use of chemotherapy. 6 Avedian et al 14 found chemotherapy to temporarily adversely affect bone growth at the bone-implant interface, however after one year they observed no differences between the two groups. Either chemotherapy has no true effect on extracortical bone growth, or the three-year follow-up period in our study is not long enough to detect the difference in ECBB between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…Literature has shown the substantial effects of doxorubicin, cisplatin, and ifosfamide on osteotomy healing and incorporation of cortical autografts, with histological evidence of poor new bone formation and decreased strength of healed osteotomies. 6 A study evaluating cortical hypertrophy around the Compress distal femoral endoprosthesis (Biomet, Warsaw, Indiana, USA) showed greater hypertrophy around the implant in patients not receiving chemotherapy in the first postoperative year. 14 In contrast, Muscolo et al 15 found that the use of chemotherapy did not have a significant effect on the overall allograft survival rates in patients undergoing reconstruction using osteoarticular allografts for musculoskeletal sarcomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation